VD_FINDINFO Décision / 2013 / 991 vom 20. Dezember 2013 - VD Tribunal cantonal (2013)
RETARD INJUSTIFIÉ, RÉCUSATION, MINISTÈRE PUBLIC, ENQUÊTE PÉNALE | 393 al. 2 let. a CPP (CH), 393 CPP (CH), 5 CPP (CH), 56 CPP (CH), 56 let. f CPP (CH)